What’s A Quail Worth? A Longitudinal Assessment of Quail Hunter Demographics, Attitudes, and Spending Habits In Texas - Jason L. Johnson; Dale Rollins; Kelly S. Reyna (National Quail Symposium Proceedings, 2017)
Funds generated and spent on the pursuit of quail (Colinus virginianus, Callipepla squamata) hunting in Texas are sizable. We surveyed a population of quail hunters in Texas in 2000 and 2011 to assess hunter demographics and spending habits. The population of hunters for the 2000 survey consisted of members of Quail Unlimited who lived in Texas while the 2011 population consisted of the former group’s successor in Texas—Quail Coalition. The initial (2000) survey was a mail questionnaire while the 2011 survey instrument was delivered electronically. We achieved response rates of 47% in 2000 but only 9% in 2011. The number of resident quail hunters in Texas decreased 72% from 1981 to 2010. Quail hunters in Texas can be characterized as white males (97%) and affluent (65% reported annual household incomes above 125,000 in 2010). Survey respondents documented an average expenditure of 8,606 in pursuit of quail during an average of 8.8 days of hunting during the 2010–2011 season. This resulted in a cost of 254 per quail bagged when combined with harvest estimates provided by respondents; an estimated increase of 23% over the last 10 years.
Keywords: Callipepla squamata; Colinus virginianus; community development; demographics; economics; hunting; northern bobwhite; scaled quail; Texas